국내 벼 논에서 메탄 기본배출계수 개발 - 김건엽; Gun Yeob Kim; 정현철; Hyun Cheol Jeong; 주옥정; Ok Jung Ju; 김희권; Hee Kwon Kim; 박준홍; Jun Hong Park; 권효숙; Hyo Suk Gwon; et al. (Hanguk hwangyeong nonghak hoeji, 2013)
BACKGROUND: Methane (CH4) emission is calculated using the default CH4 emission factor as recommended by the International Panel on Climate Change (IPCC guidelines). However, the default emission factor has been derived using including the data from other countries having different soil and environmental conditions and may not reflect the real CH4 emission rates in Korea. The objective of this study was to estimate the baseline emission factor of CH4 in Korean paddy soils during rice cultivation. METHODS AND RESULTS: Methane emission patterns were characterized in four different paddy soils across country for a consecutive 3 years during the rice cultivation period. Rice plants were cultivated under continuous flooding and fertilized using the recommended chemical fertilization in Korea (N-P2O5-K2O=90-45-57kg/ha). The mean CH4 emission rate was 2.32 kg CH4/ha/day and the uncertainty of the investigated data was 21.7%, with a valuable error range at 1.82-2.82 kg CH4/ha/day with a 95% confidence interval. CONCLUSION(S): Conclusively, the Korean paddy soils` baseline emission factor of CH4 is approximately 2.32 kg CH4/ha/day and can be used to estimate the CH4 emissions more exactly. BACKGROUND: Methane (CH4) emission is calculated using the default CH4 emission factor as recommended by the International Panel on Climate Change(IPCC guidelines). However, the default emission factor has been derived using including the data from other countries having different soil and environmental conditions and may not reflect the real CH4 emission rates in Korea. The objective of this study was to estimate the baseline emission factor of CH4 in Korean paddy soils during rice cultivation. METHODS AND RESULTS: Methane emission patterns were characterized in four different paddy soils across country for a consecutive 3 years during the rice cultivation period. Rice plants were cultivated under continuous flooding and fertilized using the recommended chemical fertilization in Korea (N-P2O5-K2O=90-45-57kg/ha). The mean CH4 emission rate was 2.32 kg CH4/ha/day and the uncertainty of the investigated data was 21.7%, with a valuable error range at 1.82-2.82 kg CH4/ha/day with a 95% confidence interval. CONCLUSION(S): Conclusively, the Korean paddy soils` baseline emission factor of CH4 is approximately 2.32 kg CH4/ha/day and can be used to estimate the CH4 emissions more exactly.